Malaria burden and costs of intensified control in Bhutan, 2006-14: an observational study and situation analysis - Kinley Wangdi, MSc; Cathy Banwell, PhD; Michelle L Gatton, PhD; Gerard C Kelly, PhD; Rinzin Namgay, BSc; Archie C A Clements, PhD (Elsevier, 2016)
Introduction: The number of malaria cases has fallen in Bhutan in the past two decades, and the country has a goal of complete elimination of malaria by 2016. The aims of this study are to ascertain the trends and burden of malaria, the costs of intensified control activities, the main donors of funding for the control activities, and the costs of different preventive measures in the pre-elimination phase (2006-14) in Bhutan. Methods: We undertook a descriptive analysis of malaria surveillance data from 2006 to 2014, using data from the Vector-borne Disease Control Programme (VDCP) run by the Department of Public Health of Bhutan's Ministry of Health. Malaria morbidity and mortality in local Bhutanese people and foreign nationals were analysed. The cost of different control and preventive measures were calculated, and the average numbers of long-lasting insecticidal nests per person were estimated. Findings: A total of 5491 confirmed malaria cases occurred in Bhutan between 2006 and 2014. By 2013, there was an average of one long-lasting insecticidal net for every 1·51 individuals. The cost of procuring long-lasting insecticidal nets accounted for more than 90% of the total cost of prevention measures. The Global Fund to Fight AIDS, Tuberculosis and Malaria was the main international donor, accounting for more than 80% of the total funds. Interpretation: The malaria burden in Bhutan decreased significantly during the study period with high coverage of long-lasting insecticidal nets. The foreseeable challenges that require national attention to maintain a malaria-free status after elimination are importation of malaria, especially from India; continued protection of the population in endemic districts through complete coverage with long-lasting insecticidal nets and indoor residual spraying; and exploration of local funding modalities post-elimination in the event of a reduction in international funding. Funding: None.